The Effect Of Ginger (Zingiber Officinale Roscoe) Consumption On Plasma Malonaldehyde And Vitamin E Concentration Of Students From Bogor - Fransiska R Zakaria; Hari Susanto; Arif Hartoyo (Jurnal Teknologi dan Industri Pangan, 2000)
Extracts of ginger contain a great number of substances having antoxidant activity. This reaserch was conducted to study the effect of ginger on malonaldehyde (MDA) as indicator of free radical and vitamin E as one of the nutrient antioxidants. Healthy student subjects were divided into treated (n=12) and control group (n=12). Treated group was suplemented with ginger drink for 30 days.At the beginning and the end of intervention, both treatment and control groups were subjected to physical health examination and their peripheral blood were with drawn for analysis of MDA (malonaldehyde) and vitamin E in plasma. Individual data from all groups revealed that treated group has significant decrease of MDA and increase of vitamin E (p